Peningkatan Keterampilan Berpikir Kreatif Siswa Kelas VIII pada Materi Adab Bertetangga melalui Metode Two Stay Two Stray di Ma’had An-Ni’mah Deli Serdang - Hasibuan, Nurainun; Lubis, Harun; Bangun, Syahria Putri Br (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to analyze the effectiveness of the Two Stay Two Stray (TSTS) method in enhancing the creative thinking skills of eighth-grade students in the topic of neighborly manners at Lembaga Pendidikan Al-Qur’an Ma’had An-Ni’mah, Deli Serdang. The research employed Classroom Action Research (CAR) with a single cycle, as the class achieved the minimum completeness target of 85%. The subjects consisted of 24 students, and data were collected through creativity tests, classroom observations, and assessments of creative thinking aspects: fluency, flexibility, originality, and elaboration. The results revealed a significant improvement in students’ creative thinking skills. Mastery learning increased from 62.5% in the pre-cycle to 91.66% in Cycle I, with the number of students reaching the completeness criterion rising from 15 to 22. Qualitative analysis showed that TSTS encouraged active interaction, idea exchange among groups, and creative collaboration through visual representation, enabling students to generate new ideas, enhance cognitive flexibility, and elaborate their concepts. This method also facilitated the internalization of Islamic adab values through meaningful creative activities. In conclusion, the TSTS method proved to be both practically effective and pedagogically relevant in improving creative thinking and understanding of neighborly adab. The study recommends implementing TSTS combined with visual media and other creative activities to strengthen students’ creativity, motivation, and collaborative skills in learning Islamic adab.